Examining the phenomenon of corruption around the world: A look over the factor that interferer in corruption perception (Research, Society and Development, 2021)
The objective of the article is to identify which variables can influence the Corruption Perception Indexes of the countries, through an analysis of the simultaneous action of variables related to social, political, legal and economic factors. The research methodology then comprises the construction of a multiple linear regression model, representative of the relationship between the Corruption Perception Indices of the countries and the set of analyzed variables. For data collection, information provided by several international internet sites (Transparency International, NationMaster database, World Bank, Fraser Institute of Economics, Freedom House and the United Nations) was accessed, from which a database was created. To perform the multiple linear regression analysis, following the assumptions of this technique and considering a model with four hypotheses. The results found showed that, when analyzed simultaneously, the statistically significant variables of the model (p-value0.10) that they influence the Corruption Perception Indices. The research addressed here helps public policy makers in countries to design public policies that aim to positively influence their Corruption Perception Index.